System matrix computation for iterative reconstruction algorithms in spect based on direct measurements - Borys, Damian; Szczucka-Borys, Katarzyna; Gorczewski, Kamil (Zielona Góra: Uniwersytet Zielonogórski)
A method for system matrix calculation in the case of iterative reconstruction algorithms in SPECT was implemented and tested. Due to a complex mathematical description of the geometry of the detector set-up, we developed a method for system matrix computation that is based on direct measurements of the detector response. In this approach, the influence of the acquisition equipment on the image formation is measured directly. The objective was to obtain the best quality of reconstructed images with respect to specified measures.
Keywords: SPECT; iterative reconstruction; quantitative imaging